Sensing, territory, population: Computation, embodied sensors, and hamlet control in the Vietnam War. (October 2019) - Belcher, Oliver
This article analyses a mid-20th century computerized pacification reporting system, the Hamlet Evaluation System (HES), used by the US military to measure hamlet-level security and development trends in the Vietnam War. The significance of the HES was its capacity to translate US Military Advisor observations of Vietnamese hamlet life into a machine-readable format used by US military systems analysts to disclose 'patterns of life.' I show how US Military Advisors operated as 'embodied sensors' within the HES, producing a distinctive location-based event ontology – a 'view of below' – accompanied by rudimentary digital maps in-formation from incoming hamlet-level observation streams. I argue that acts of translating the rich texture of hamlet and village life into an objectified information format constituted a unique form of 'epistemic violence, ' rooted not so much in the narrative subjection of the 'Other, ' but in the pure abstraction of life into a digitally stored data trace.